Connectivity, flows and dynamics of reconfiguration in Brazilian broadcasters in face of the digital ecosystem - Stefano, Luiza de Mello; Ferreira Vieira, Soraya Maria (COMUNICACIÓN. Revista Internacional de Comunicación Audiovisual, Publicidad y Estudios Culturales, 2020)
Analizamos cómo los principales canales brasileños de televisión pública y privada (ESPN Brasil, GNT, Rede Globo y Multishow) amplían lenguajes desde el surgimiento del ecosistema de comunicación conectiva, en el que la televisión y la web entran en simbiosis. La carrera para promover estrategias y traer participación proporcionó escenarios que cambian la fluidez en la ecología digital. Concluimos que a pesar de los cambios para este nuevo escenario aún son inciertas, hay una clara preocupación por parte de las emisoras brasileñas en proponer acciones para ser más atractivas y adecuadas al actual contexto televisivo. --- We analyze how the main Brazilian channels of public and private TV - ESPN Brasil, GNT, Rede Globo and Multishow - are expanding languages from the emergence of the connective communication ecosystem, in which television and web enter symbiosis. The race to promote strategies and bring engagement provided scenarios that change fluidity in digital ecology. We conclude that although changes to this new scenario are still uncertain, there is a clear concern on the part of Brazilian broadcasters to propose actions to be more attractive and appropriate to the current television context.